2019
DOI: 10.15369/sujms.31.365
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Protein Profiles of Gingival Crevicular Fluids Collected from Incisors, Canines, and Molars

Abstract: Many studies have shown that gingival crevicular uid GCF re ects the in ammatory state of local periodontal tissues. GCF has been collected from several types of teeth in previous studies. However, there is no report that characterizes GCF by the type of tooth. In the present study, the protein pro les of GCF from different sites were comprehensively compared with each other. GCF was sampled from six healthy adult men 21-31 years old with healthy periodontal tissues. Three separate GCF samples were collected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Apolipoprotein A-1 (ApoA-1) is the major protein component of high-density lipoprotein (HDL) (34). It was detected in both groups demonstrating no significant difference, similar to the studies identify ApoA-1 in their analysis (Table 4) (8,23,25,29,35). Only Moriya et al (28) reported that the ApoA-1 level was upregulated in the GCF of the permanent teeth compared to the primary teeth.…”
Section: Discussionsupporting
confidence: 52%
“…Apolipoprotein A-1 (ApoA-1) is the major protein component of high-density lipoprotein (HDL) (34). It was detected in both groups demonstrating no significant difference, similar to the studies identify ApoA-1 in their analysis (Table 4) (8,23,25,29,35). Only Moriya et al (28) reported that the ApoA-1 level was upregulated in the GCF of the permanent teeth compared to the primary teeth.…”
Section: Discussionsupporting
confidence: 52%